Pengaruh Lingkungan Kerja Non Fisik terhadap Kinerja Karyawan Badan Pengusahaan Kawasan Perdagangan Bebas dan Pelabuhan Bebas Batam - Abiyyah Hanan Ramadhani; Badia Perizade; Yulia Hamdaini Putri (JEMBATAN, 2022)
The aims of this study to establish the influence of non-physical environment on employee performance at Badan Pengusahaan Kawasan Perdagangan Bebas dan Pelabuhan Bebas Batam. The sample used a random sampling technic on 96 of total respondents. This research used a quantitave method with questonnaires approach as aplliance of data collection, while the data analysis technique uses simple linear regression analysis. Based on results used simple linear regression data analysis it can be concluded that Non-Physical Environment (X) has a significant effect on Employee Performance (Y) at Badan Pengusahaan Kawasan Bebas dan Pelabuhan Bebas Batam. Badan Pengusahaan Batam is expected to keep maintaining of their worker relationship in harmonious to raise up the enjoyable atmosphere around the worker with the result that the worker are capable to preserve their performances level in order to remain in the best position. For further research to consider conduct research using other variables on performance such as rewards and recognition, self-development and training and promotion